Female Genital Schistosomiasis Lesions Explored Using Circulating Anodic Antigen as an Indicator for Live Schistosoma Worms - Nemungadi, Takalani Girly; Kleppa, Elisabeth; van Dam, Govert J.; Corstjens, Paul L. A. M.; Galappaththi-Arachchige, Hashini Nilushika; Pillay, Pavitra; Gundersen, Svein Gunnar; Vennervald, Birgitte J.; Ndhlovu, Patricia; Taylor, Myra; Naidoo, Saloshni; Kjetland, Eyrun F. (Frontiers in Tropical Diseases, 2022)
Background In areas where reinfection with schistosomiasis is rampant, it is not known if the lesions of Female Genital Schistosomaisis are a consequence of live worms, or caused by dead ova. Live schistosome worms regurgitate Circulating Anodic Antigen (CAA). We sought to explore the association between the different lesions of FGS (grainy sandy patches, homogenous yellow patches, rubbery papules and abnormal blood vessels) and the presence of live worms as indicated by S. haematobium-derived CAA in blood. Materials and Methods In this cross-sectional study, rural high schools were randomly selected from Ilembe, uThungulu and Ugu Districts on the East Coast of South Africa, KwaZulu-Natal Province. Serum samples for CAA analysis were collected from 246 female learners aged 16 - 23 years. Uncorrected chi-square and odds ratio with 95% confidence interval (CI) were used to evaluate the null hypothesis. Results CAA was positive in 82/246 (33%) of the participants. Sandy patches were found in 123 (50%) of the study population. Grainy sandy patches were significantly associated with CAA even after controlling for age (Adjusted Odds Ratio (AOR) 4.2, 95% CI 2.3 - 7.9, p < 0.001). Likewise, abnormal blood vessels were associated with CAA (AOR 3.0, 95% CI 1.5-4.5, p = 0.001) whereas homogenous yellow patches were not associated with CAA (p = 0.57). Rubbery papules were not found in this study population. Conclusion Grainy sandy patches and abnormal blood vessels are found more commonly in women who harbour live Schistosoma haematobium worms whilst homogenous yellow patches may indicate chronic tissue damage due to dead ova.